Topographical and Thematic Perspectives in the Latin Poetry of the First Anglo-Norman Kings - Roberto Angelini (Tabularia)
This study deals with Norman poetry: it examines the authors, the texts, and especially the literary genres to which they belonged, in the period between the XIth and XIIth centuries. Following a chronological order, the analysis starts from XIth-century Normandy: the main political and religious centres, Rouen, Caen and Le Bec, were also the most important places of poetic output. Most of these writings are hagiographies or encomia of important figures in the ducal and royal courts. In this regard, Serlo of Bayeux stands out as a clear example: his poems are valuable historical evidence for the Norman relationship with the English and their king in 1105-1106. In England, after the bold enterprise of William the Conqueror, Norman, Flemish, French and Italian learned men had a very important role in cultural life. York and Canterbury were the most prominent centres for versification. The study ends by focusing on the numerous verses contained in the historical works of Orderic Vitalis, William of Malmesbury and Henry of Huntingdon.